Archiwum klonów starych drzew sosny zwyczajnej w Puszczy Knyszyńskiej - Korczyk, Adolf (Leśne Prace Badawcze, 2010)
Between 1986–1990 the inventory of old trees was carried out in the Knyszynska Primeval Forest. In total 47 pines were described; they grew on the fresh coniferous forest (Bśw), fresh mixed coniferous forest (BMśw) and fresh broadleaved forest (LMśw) and reached average height of 31 m, mean diameter breast height (DBH) of 75,3 cm and age at breast height among 223 to 302 years. The vegetative progeny was obtained from 36 pines using grafting. Grafted trees were planted in 1994 and 2004 and clone archive was made in the compartment number 170 h of the Supraśl Forest District. After 12 years of growth the survival rate calculated in spring 2007 reached 22,64% of total grafts (in particular years from 10,53% to 72,41%.